Long-term day-and-night rotating shift work poses a barrier to the normalization of alanine transaminase. (May 2014) - Lin, Yu-Cheng; Hsieh, I-Chun; Chen, Pau-Chung
Abstract : To evaluate the impact of day-and-night rotating shift work (RSW) on liver health, we performed a retrospective analysis of the association between long-term RSW exposure and the normalization of plasma alanine transaminase (ALT) levels over a five-year period. The data from physical examinations, blood tests, abdominal sonographic examinations, personal histories, and occupational records were collected from a cohort of workers in a semiconductor manufacturing company. The sample population was divided into three subgroups for analysis, according to self-reported shift work status over the five-year interval: persistent daytime workers, workers exposed intermittently to RSW (i-RSW), and workers exposed persistently to RSW (p-RSW). Records were analyzed for 1196 male workers with an initial mean age of 32.5 years (SD 6.0 years), of whom 821 (68.7%) were identified as rotating shift workers, including 374 i-RSW (31.3%) and 447 p-RSW workers (37.4%). At the beginning of the follow-up, 275 were found to have elevated ALT (e-ALT): 25.1% daytime workers, 23.0% i-RSW workers, and 21.3% p-RSW workers ( p  = 0.098). Of those with e-ALT at the beginning, 101 workers showed normalized serum ALT levels at the end of five-year follow-up: 40 (10.7%) of 375 daytime workers, 32 (8.6%) of 374 i-RSW workers, and 29 (6.5%) of 447 p-RSW workers ( p  = 0.016). Compared with the workers having persistent e-ALT at the end of follow-up, the workers normalized serum ALT levels had significantly lesser exposures to RSW during follow-up. By performing multivariate logistic regression analyses, and comparing with the persistent daytime co-workers, after controlling for confounding variables (age, occupational factors, educational levels, lifestyle factors, metabolic syndrome, hepatovirus infection, and fatty liver), analysis indicated that the workers exposed to p-RSW were 46% less likely (OR, 0.54; 95% CI, 0.30–0.95; p  = 0.03) to attain normal ALT levels within a five-year interval. These observations demonstrate that persistent day-and-night RSW pose a vigorous obstacle to the normalization of e-ALT among workers with preexisting abnormal liver function. We suggest that workers and managers approach with caution the consideration of assigning or accepting long-term day-and-night RSW when an employee health screening shows evidence of abnormal liver function.